Computational EPAS1 rSNP Analysis, Transcriptional Factor Binding Sites and High Altitude Sickness or Adaptation - E. Buroker, Norman (Journal of Proteomics and Genomics Research, 2016)
Purpose The endothetal Per-Arnt-Sim (PAS) domain protein 1 (EPAS1) gene which encodes hypoxia-inducible-factor-2 alpha (HIF2a) is a transcription factor that is involved in the response to hypoxia. EPAS1 has been found to have four (rs56721780, rs6756667, rs7589621, rs1868092) simple nucleotide polymorphisms (SNPs) associated with human disease.These SNPs were computationally examined with respect to changes in potential transcriptional factor binding sites (TFBS) and these changes were discussed in relation to disease and alterations in high altitude adaptation in humans. Methods The JASPAR CORE and ConSite databases were instrumental in identifying the TFBS. The Vector NTI Advance 11.5 computer program was employed in locating all theTFBS in theEPAS1 gene from 1.6 kb upstream of the transcriptional start site to 539 bps past the 3’UTR. The JASPAR CORE database was also involved in computing each nucleotide occurrence (%) within the TFBS. Results The EPAS1 SNPs in the promoter, intron two and the 3’UTR regions have previously been found to be significantly associated with disease and different levels of high-altitude hypoxia among native Tibetans. The SNP alleles were found to alter the DNA landscape for potential transcriptional factors (TFs) to attach resulting in changes in TFBS and thereby, alter which transcriptional factors potentially regulate the EPAS1 genesuch as for the glucocorticoid and mineralocorticoid nuclear receptor binding sites created by the rs7589621 rSNP EPAS1-G allele. These receptors regulate carbohydrate, protein and fat metabolism. Also the minor rs7589621 rSNP EPAS1-A creates a punitive TFBS for the FOXC TF which is an important regulator of cell viability and resistance to oxidative stress. These EPAS1 SNPs should be considered as regulatory (r) SNPs. Conclusion The alleles of each rSNP were found to generate unique TFBS resulting in potential changes in TF EPAS1 regulation. The punitive changes in TFBS created by the four rSNPs could very well influence the significant cline in allele frequencies seen in Tibetans with increasing altitude or the haplotype association with high altitude polycythemia in male Han Chinese. These regulatory changes were discussed with respect to changes in human health that result in disease and sickness.
Keywords: EPAS1; rSNPs; TFBS; disease; sickness